2021
DOI: 10.1021/acsami.1c03465
|View full text |Cite
|
Sign up to set email alerts
|

NOx Storage Performance at Low Temperature over Platinum Group Metal-Free SrTiO3-Based Material

Abstract: Pt-based catalysts are commonly employed as NO x -trapping catalysts for automobiles, while perovskite oxides have received attention as Pt-free NO x -trapping catalysts. However, the NO x storage performance of perovskite catalysts is significantly inferior at low temperatures and with coexisting gases such as H2O, CO2, and SO2. This study demonstrates that NO x storage reactions proceed over redox site (Mn, Fe, and Co)-doped SrTiO3 perovskites. Among the examined catalysts, Mn-doped SrTiO3 exhibited the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…SrTi 1– x Co x O 3−δ ( x = 0, 0.2, 0.4, 0.6, and 0.8) and Ce 0.5 Zr 0.5 O 2 (CZ), a benchmark OSM, were synthesized by the Pechini method. , Citric acid (400 mmol, 98.0%) was dissolved in deionized water (180 mL), and starting materials were added to a citric acid solution. The starting materials were used as follows: SrCO 3 (20 mmol, 99.0%), titanium­(IV) tetraisopropoxide (20­(1 – x ) mmol, 95.0%), Co­(NO 3 ) 2 ·6H 2 O (20 x mmol, 98.0%), Ce­(NO 3 ) 3 ·6H 2 O (10 mmol, 98.0%), and ZrO­(NO 3 ) 2 ·2H 2 O (10 mmol, 97.0%).…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…SrTi 1– x Co x O 3−δ ( x = 0, 0.2, 0.4, 0.6, and 0.8) and Ce 0.5 Zr 0.5 O 2 (CZ), a benchmark OSM, were synthesized by the Pechini method. , Citric acid (400 mmol, 98.0%) was dissolved in deionized water (180 mL), and starting materials were added to a citric acid solution. The starting materials were used as follows: SrCO 3 (20 mmol, 99.0%), titanium­(IV) tetraisopropoxide (20­(1 – x ) mmol, 95.0%), Co­(NO 3 ) 2 ·6H 2 O (20 x mmol, 98.0%), Ce­(NO 3 ) 3 ·6H 2 O (10 mmol, 98.0%), and ZrO­(NO 3 ) 2 ·2H 2 O (10 mmol, 97.0%).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Then, we investigated the chemical stability of Sr–Fe materials and found that Ti doping into Fe sites in SrFeO 3−δ dramatically suppressed SrCO 3 formation and improved the oxygen storage rate . Furthermore, in the context of the NO oxidation activity over SrTi 0.8 B 0.2 O 3 (B = Mn, Fe, and Co), the lattice oxygen in Co-doped SrTiO 3 materials has recently been shown to have extremely high reactivity with NO, compared to that of Mn- or Fe-doped materials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding has also been reported about Mn-doped SrTiO 3 showing higher NO x storage capacity than SrTiO 3 . 46…”
Section: Resultsmentioning
confidence: 99%
“…A similar finding has also been reported about Mn-doped SrTiO 3 showing higher NO x storage capacity than SrTiO 3 . 46 To further understand the NO x adsorption mechanism, the in situ DRIFTS of NO + O 2 on Mn 1 Fe 2 -450 was performed, and the results are shown in Fig. 9.…”
Section: Reaction Mechanism Analysismentioning
confidence: 99%